Tocilizumab in the treatment of systemic juvenile idiopathic arthritis - Murakami, Miho (Open Access Rheumatol, 2012)
Systemic juvenile idiopathic arthritis is one of the common rheumatic diseases in childhood and characterized by spiking fever, evanescent skin rash, lymphadenopathy, hepatosplenomegaly, and serositis, in addition to arthritis. Children with systemic juvenile idiopathic arthritis often show growth retardation and developmental abnormality, as well as macrophage activation syndrome, a life-threatening complication. Overproduction of interleukin-6 is pathologically responsible for the systemic inflammatory manifestations and abnormal laboratory results with systemic juvenile idiopathic arthritis. Thus, tocilizumab, a humanized antihuman interleukin-6 receptor antibody, has been developed as a therapeutic agent for the disease. A series of clinical studies have demonstrated the excellent efficacy and safety of tocilizumab for patients with active disease. Tocilizumab was approved for systemic juvenile idiopathic arthritis in Japan in 2008 and in the European Union and the United States in 2011.